NILAI RERATA SINGLE BREATH COUNT TEST DAN PEAK EXPIRATORY FLOW RATE PADA PASIEN SKOLIOSIS DI RSUD ULIN BANJARMASIN - Hasna, Usratul; Hayati, Azka; Asnawati, Asnawati; Siddik, Muhammad; Marisa, Dona (Homeostasis, 2024)
Abstract: Scoliosis is a three-dimensional vertebral disorder in the form of an abnormal curvature laterally affecting one or more segments of the thoracolumbar vertebral column by forming the letter "S" or "C. Scoliosis can affect several factors, namely thoracic volume, diaphragm function, and airway resistance. This study aims to determine the mean value of single breath count test and peak expiratory flow rate in patients with scoliosis at Ulin Banjarmasin Hospital. This study is a descriptive study with a cross sectional design, the samples taken were patients diagnosed with scoliosis at Ulin Banjarmasin Hospital in the November-December 2023 period. The results of this study obtained the average mean results of SBCT in scoliosis patients of 37.6 and PEFR in scoliosis patients of 263.3 L/min. It can be concluded that the SBCT value in scoliosis patients at Ulin Banjarmasin Hospital is included in the normal category but the PEFR value in scoliosis patients is included in the abnormal category. Keywords: scoliosis, single breath count test, peak expiratory flow rate Abstrak: Skoliosis adalah suatu kelainan vertebra tiga dimensi berupa lengkungan abnormal ke arah lateral yang mempengaruhi satu atau lebih segmen kolom vertebra thorakolumbal dengan membentuk huruf “S” atau “C. Skoliosis dapat mempengaruhi beberapa faktor yaitu volume toraks , fungsi diafragma, dan resistensi saluran napas. Penelitian ini bertujuan untuk mengetahui nilai rerata single breath count test dan peak expiratory flow rate pada pasien skoliosis di RSUD Ulin Banjarmasin. Penelitian ini merupakan penelitian deskriptif  dengan desain cross sectional, Sampel yang diambil merupakan pasien yang didiagnosis skoliosis di RSUD Ulin Banjarmasin periode November-Desember 2023. Hasil dari penelitian ini diperoleh rerata hasil rerata dari SBCT pada pasien skoliosis sebesar 37,6 dan PEFR pada pasien skoliosis sebesar 263,3 L/menit Dapat disimpulkan bahwa nilai SBCT pada pasien skoliosis di RSUD Ulin Banjarmasin termasuk dalam kategori normal tetapi nilai PEFR pada pasien skoliosis termasuk dalam kategori tidak normal Kata-kata kunci: skoliosis, single breath count test, peak expiratory flow rate